Experimental Investigation on the Hydrodynamic Performance of Submerged Porous Triangular Breakwater - Islam, Md Ashraful; Bashirul Islam, Md; Ul Haque, Sajjad; Abir, Omar (Journal of Engineering Science, 2025)
This study examines the performance of submerged triangular breakwaters with varying heights and porosities in a two-dimensional wave flume. Experiments were conducted using breakwaters of 10 cm, 12 cm, and 14 cm heights under four wave conditions, with a constant water depth of 15 cm. Water surface elevations were recorded at five locations around the breakwater. Results show that relative breakwater height (h/d) and porosity (n) significantly influence wave transmission. The transmission coefficient (Kt) decreased to a minimum of 0.32 for a solid breakwater at h/d = 0.93. The reflection coefficient (Kr) peaked at 0.43 for a 14 cm solid breakwater. Porosity had minimal effect on reflection but significantly influenced energy dissipation, which reached a maximum (Kd = 0.95) for highly submerged solid breakwaters. Regression analysis confirmed the role of porosity and breakwater width on wave behavior. These findings support the effective design of submerged breakwaters for coastal protection. Journal of Engineering Science 16(1), 2025, 69-80